Development of a novel DNA sequencing method not only for hepatitis B virus genotyping but also for drug resistant mutation detection - Wang Fanjun; Lu Lili; Yu Changshun; Lv Zhanwu; Luo Xuelian; Wan Chao; Hu Zhaohui; Zhu Qinyi; Deng Youping; Zhang Chuyu (BMC, 2013)
Abstract Background In HBV-infected patients, different genotypes of the hepatitis B virus influence liver disease progression and response to antiviral therapy. Moreover, long-term antiviral therapy will eventually select for drug-resistant mutants. Detection of mutations associated to antiviral therapy and HBV genotyping are essential for monitoring treatment of chronic hepatitis B patients. Results In this study, a simple method of partial-S gene sequencing using a common PCR amplification was established for genotyping clinical HBV isolates sensitively, which could detect the drug-resistant mutations successfully at the same time. Conclusions The partial S gene sequencing assay developed in this study has potential for application in HBV genotyping and drug resistant mutation detection. It is simpler and more convenient than traditional S gene sequencing, but has nearly the same sensitivity and specificity when compared to S gene sequencing.